2009
DOI: 10.1086/595791
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Colitis Increases Susceptibility to Oral Prion Disease

Abstract: Dietary exposure to prion-contaminated materials has caused kuru and variant Creutzfeldt-Jakob disease in humans, and transmissible spongiform encephalopathies (TSEs) of cattle, mink, and felines. The epidemiology of dietary prion infections suggest that host genetic modifiers, and possibly exogenous cofactors, may play a decisive role in determining disease susceptibility. However, few cofactors influencing prion susceptibility have been identified. Here we investigated whether colitis might represent one suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 50 publications
1
33
2
Order By: Relevance
“…In contrast, mice lacking this molecule demonstrated marked elevations in several proinflammatory cytokine transcripts and pro-apoptotic regulatory proteins, factors predicted to exacerbate colitis. As reported by Sigurdson et al,30 who demonstrated increased PrP C expression in the inflamed colons of Salmonella-infected mice, we observed that DSS-induced colitis increased PrP C expression from the endogenous locus. Expression of PrP C from the Tga20 transgene was also up-regulated, which suggests that the necessary regulatory elements were present in the Prnp promoter fragment used in the vector.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In contrast, mice lacking this molecule demonstrated marked elevations in several proinflammatory cytokine transcripts and pro-apoptotic regulatory proteins, factors predicted to exacerbate colitis. As reported by Sigurdson et al,30 who demonstrated increased PrP C expression in the inflamed colons of Salmonella-infected mice, we observed that DSS-induced colitis increased PrP C expression from the endogenous locus. Expression of PrP C from the Tga20 transgene was also up-regulated, which suggests that the necessary regulatory elements were present in the Prnp promoter fragment used in the vector.…”
Section: Discussionsupporting
confidence: 88%
“…Although acute colitis can accelerate the onset of disease after oral challenge with infectious prions, 30 a physiologic role for PrP C in colitis has not been reported. We, therefore, examined the role of PrP C in mice either lacking or overexpressing this protein in the dextran sulfate sodium (DSS)-induced model of experimental colitis.…”
mentioning
confidence: 99%
“…An independent study has reported that congruent infection with Salmonella typhimurium exacerbated oral prion disease (Sigurdson et al, 2009). In this study, the effects on prion disease pathogenesis were attributed to the acute inflammation that infection with the bacterium causes in the colon.…”
Section: Congruent Pathogen Infection In the Large Intestinementioning
confidence: 69%
“…For example, lesions to the mucosa can enhance the oral transmission of prions (Denkers et al, 2011). Pathogen exposure can also modify the expression of PrP C and innate immunity genes in the gut mucosa (Dervishi et al, 2015;Sigurdson et al, 2009). Therefore, gastrointestinal pathogen-mediated damage to the gut mucosa may exacerbate disease pathogenesis by enhancing prion uptake from the lumen.…”
Section: Effects Of Congruent Gastrointestinal Pathogen Infection On mentioning
confidence: 99%
“…Ultimately, this could lead to accelerated PrP Sc replication during immune responses. Interestingly, the presence of bacterial colitis has recently been shown to increase susceptibility to oral prion infection [80]. It is important to note, however, that several studies appear to directly refute this conclusion.…”
Section: Shortly After Prpmentioning
confidence: 99%